Cutaneous mantle cell lymphoma histomorphologically mimicking subcutaneous panniculitis‐like T‐cell lymphoma: Case report. (3rd May 2019) - Laggis, Caroline; Miles, Rodney; Stephens, Deborah M.; Duffy, Keith; Bowen, Anneli; Wada, David
Abstract: Secondary cutaneous involvement by mantle cell lymphoma (MCL), an uncommon aggressive B‐cell malignancy, predominantly involves the dermis, with few reports of pannicular involvement. Lymphocytic infiltration of subcutaneous tissue is associated with inflammatory panniculitides and certain T‐cell lymphomas, primarily subcutaneous panniculitis‐like T‐Cell lymphoma (SPTCL), which is characterized by rimming of adipocytes by tumor cells. We report the case of a 69‐year‐old man with a history of systemic nodal MCL who presented with subcutaneous nodules on his lower extremities after receiving multi‐agent chemotherapy. Biopsies showed a dense infiltrate of atypical, mitotically active, monomorphic, medium‐sized lymphoid cells in the subcutaneous fat with prominent rimming of the adipocytes by the tumor cells. These features were not morphologically typical of MCL. Immunohistochemistry showed these cells to be CD20+, CD5+ B‐cells with strong cyclin D1 expression; fluorescence in situ hybridization (FISH) analysis was positive for t(11;14)(q13;32), confirming the diagnosis of secondary cutaneous involvement of MCL. This represents an exceptional report of cutaneous MCL presenting clinically and histologically with a panniculitis‐type pattern and adipocyte rimming, histomorphologically mimicking SPTCL. Noteworthy examples, such as this report, support the practice of utilizing clinical correlation, immunohistochemistry, and/or molecular cytogenetics to confirm the diagnosis of any case suspicious for cutaneous lymphoma.